Priorities of sectoral structure of industry of Kazakhstan (Journal of Economic Research & Business Administration, 2015)
The economy of state can be considered as a portfolio of projects. These projects should be profitable and efficient. State must strive to increase such projects and be interested in the growth of profitability and efficiency of projects already under implementation. Main criteria determining top-priority sectors of economy are as follows: competitive advantages of state on international market or competitive advantages that will appear in future, high value added of output product as a key incentive for support of top-priority sector, orientation to export, multiplicative effect, social significance, technological and innovative prospects of development. Excessive ambiguity in priorities can lead to, firstly, depletion of budget, secondly, inefficient concentration of efforts, which will ultimately lead to absence of any result. Calculations of specialization ratios that can help determine top-priority sectors of Kazakhstan industry are set out in this piece of work.
Keywords: top-priority sector; specialization of regions; manufacturing industry; specialization ratios